SLANG DALAM FILM CENTRAL INTELLIGENCE KARYA RAWSON MARSHALL THURBER - SOLIHIN, USMAN S. (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2017)
ABSTRACT Language has an important function in societyâ€™s life. This research design entitled â€œSlang in the Film Central Intelligence by Rawson Marshall Thurberâ€ is an attempt to identify the slangs found in the Film Central Intelligence, analyze and describe their forms and meanings. The writer also uses some theories that related to slang language and the definition of slang. The theory used in this research is by Bloomfield, Patridge, and Guth. Theoretically, the writer hopes this research can give contribution to linguistic especially on sociolinguistics field more specially on slang. The writer uses inductive method to analysis the data in this research. From the analysis, the writer selects six types of slang, they are: Shortened, Interjection, Society slang, Public house slang, Figurative Expression, and Nick Name. From this research, the result show that there are 5 slangs in Shortened form, 5 slangs in Interjection form, 30 slangs in Society slang, 5 slangs in Public house slang, 2 slangs in Figurative Expression, and 4 slangs in Nick Name. Â Â Keywords: Slang,Â film Central Intelligence, Bloomfield , Patridge, Guth